TAFSIR SURAT AN-NISA AYAT 34 TENTANG TANGGUNG JAWAB PENCARI NAFKAH PERSPEKTIF MUFASSIR INDONESIA - Rokhmah, Siti; Nurseha, Muhammad Achid (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2023)
This study aims to find out the thoughts and interpretations according to Sheikh Nawawi Al-Bantani in Tafsir Marāh Labid, Prof. Dr. Hamka in Tafsir Al-Azhār, and Prof. Dr. M. Quraish Shihab in Tafsir Al-Misbāh about the responsibility of breadwinners in the family seen from QS. An-Nisa verse 34. In addition, to know the relevance of Sheikh Nawawi Al-Bantani's interpretation in Tafsir Marāh Labid, Prof. Dr. Hamka in Tafsir Al-Azhār, and Prof. Dr. M. Quraish Shihab in Tafsir Al-Misbāh about the responsibility of providing for the family seen from QS. An-Nisa verse 34 with the present age.Research on dTafsir QS. An-Nisa Verse 34 on the Responsibility of Breadwinners The perspective of Indonesian Mufassir (Sheikh Nawawi Al-Bantani in Tafsir Marāh Labid, Prof. Dr. Hamka in Tafsir Al-Azhār, and Prof. Dr. M. Quraish Shihab in Tafsir Al-Misbāh)d is included in the category of literature (Library Research), where all materials and information needed are sourced from literature materials and books, be it the Qur'an, the book of tafsir or any other work relevant to this research.The results of this study, interpretation (Sheikh Nawawi Al-Bantani in Tafsir Marāh Labid, Prof. Dr. Hamka in Tafsir Al-Azhār, and Prof. Dr. M. Quraish Shihab in Tafsir Al-Misbāh) in QS. An-Nisa verse 34, it is the husband who is responsible for making a living in the family. This is because the husband acts as the leader or head of the household. Interpretation (Sheikh Nawawi Al-Bantani in Tafsir Marāh Labid, Prof. Dr. Hamka in Tafsir Al-Azhār, and Prof. Dr. M. Quraish Shihab in Tafsir Al-Misbāh) in QS. An-Nisa verse 34 related to the responsibility of the breadwinner, is still relevant today.